A Modified Method for the Assay of Factor IX - Sen, N. N; Sen, Radharani; Denson, K. W. E; Biggs, Rosemary (Thrombosis and Haemostasis, 1967)
A modification of the method for the assay of factor IX proposed by Biggs et al. (1961) (1) is described. The modification is likely to prove more reliable than the original method.